S43 Real World Experience Of The Use Of Pet-ct For Distinguishing Between Benign Pleural Disease And Malignant Mesothelioma. (10th November 2014) - Prior, K; Fingleton, J; Howell, T
Abstract : Patients presenting with pleural disease on a background of asbestos exposure pose a diagnostic dilemma. Malignant mesothelioma and benign pleural disease have similar radiological appearances but markedly different prognoses. Definitive histological diagnosis is gold standard, however, there are small case series where PET-CT has been compared to pleural biopsy. These have suggested cut-off standardised uptake values (SUV) of 2.0–3.0, with reported sensitivity of 94.1–100% and specificity of 94–100% for excluding pleural malignancy. It has been suggested that where the CT appearances are more in keeping with a benign aetiology, pleural avidity on PET-CT may be able to adequately distinguish between benign and malignant disease, identifying a low-risk population that can be observed in preference to proceeding to thoracoscopy. We are a cardiothoracic centre which utilises PET-CT in this way. We aimed to review our single-centre experience to see if our outcomes were consistent with the reported data. All PET-CT reports carried out since 2007 with the mention of pleura/pleural within the request or report were reviewed. Radiological reports and patient records were examined, scans requested primarily for assessment of the pleura were included. Indication, radiological diagnosis, final diagnosis, presence of histological confirmation and duration of follow-up were determined. All patients with at least 6 months follow-up were analysed. 185 PET CT scan reports were reviewed, of which 28 were carried out primarily for assessment of pleural disease. 9 were found to have high SUVs suggestive of malignancy. 7 of which were demonstrated to be mesothelioma, 1 pleural tumour, 1 recurrence of non-small cell lung cancer. The remaining 19 were reported to have low SUVs, consistent with benign pleural disease. For those with PET findings consistent with benign pleural disease, follow up data was available for a median of 12 months (Min 6- Max 66). One patient underwent pleural biopsy, which was consistent with benign disease. None of those designated as benign pleural disease based on PET-CT appearances were subsequently found to have pleural malignancy. Our findings are consistent with previously published data and support the utility of PET-CT scanning in differentiating benign from malignant pleural disease in a clinical setting.